Office and administrative management : systems analysis, data processing, and office services - Littlefield, C. L.; Rachel, Frank M.; Caruth, Donald L. (New Delhi : Prentice-Hall of India, 1971)
The book concerns itself with work systems and social systems or human relationships upon which all other systems depend heavily for the success of any administrative management. Means of selecting, training, and motivating employees, as well as administering a effective personnel programme are presented and examined.
Published in 1956 under title: Modern office management.
Includes bibliographical references and index.
oif 28/01/2019
Loans
Keywords: Office management; Management information systems; Business